Late onset middle ear neuroendocrine tumor presenting with distant metastasis - Federica Pollastri; Rudi Pecci; Elisa Pellegrini; Paolo Vannucchi; Cecilia Taverna; Beatrice Giannoni (Otolaryngology Case Reports, 2021)
Tumors of the ear with neuroendocrine features are a very rare group of neoplasms, with neuroendocrine adenoma representing the more frequent entity found; the prevalence of middle ear neuroendocrine tumors is so low that it has never been determined exactly.Herein we describe the case of a 74 years old woman who presented a pure moderately differentiated middle ear neuroendocrine tumor after a long history of adhesive otitis media. Patient abruptly developed otalgia and a sense of plugged ear. Otomicroscopy revealed a polypoid mass of the external auditory canal. On histopathologic exam a neoplastic proliferation of monomorphous epithelioid cells arranged in small nests and clusters was present, being positive to cytokeratins, chromogranin, synaptophysin and CD56, and negative to S100. Ki-67 proliferation index was 20%. The lesion was diagnosed as a moderately differentiated neuroendocrine tumor (NET grade 2). CT and PET scans highlighted the concurrent presence of locoregional lymph nodes involvement but also at distance liver metastases.The patient underwent chemotherapy and liver repetitions were treated locally. At the time of the writing the patient is in good general condition.We describe an exceeding rare case of a moderately differentiated neuroendocrine tumor with primitivity in the middle ear and concurrent distant metastasis at the time of the diagnosis.This case represents a clinical and histological challenge, for the rarity of the lesion and the aspecific symptoms of the patient.